Rough Waters : American Involvement with the Mediterranean in the Eighteenth and Nineteenth Centuries. - Marzagalli, Silvia (Research in Maritime History LUP., 2017)
This study analyses the presence of American ships, merchants, and interests in the Mediterranean region in the first decades following the independence of the United States, and seeks to understand whether or not the English, Dutch, Scandinavians, and Americans invaded the region and its shipping industry in the eighteenth and nineteenth centuries.